Hubungan Kualitas Pelayanan Dan Kompetensi Pegawai Dengan Kepuasan Layanan Kependudukan Pak Kades Mantap - Karningsih Karningsih; Sugiyanto Sugiyanto (Public Service and Governance Journal, 2024)
Population administration services in general have not been able to provide satisfaction to the community using population services, for various reasons that are not acceptable to the community, so a form of service that is easy and can be accessed by the community is needed without having to come to the population service center, therefore a comprehensive service is needed. online with the” Pak Kades Mantap” population service program, which is supported by employee competence so that people can get population documents easily and fast. The sample collection technique used is the incidental technique. The data analysis used in this research is qualitative and quantitative analysis. This type of research uses the explanatory type. This shows that the higher the quality of service and competency of the employees, the higher the satisfaction with the population service "Pak Kades Mantap" at the Rejosari Village Office, Kangkung District, Kendal Regency